Early and dynamic detection of doxorubicin induced cardiotoxicity by myocardial contrast echocardiography combined with two-dimensional speckle tracking echocardiography in rats - Zhang, Jun; Li, Xin; Liu, Juan; Shang, Yongning; Tan, Lin; Guo, Yanli (Frontiers in Cardiovascular Medicine, 2023)
Background Anthracycline-induced cardiotoxicity is well-known as a side effect of chemotherapy. Currently, clinical imaging techniques are not capable to detect doxorubicin (DOX)-induced cardiotoxicity before a functional decline. The purpose of this study was to evaluate whether myocardial contrast echocardiography (MCE) can dynamically monitor the cardiac changes in the early stage in the DOX-induced rat model of cardiotoxicity. Methods A weekly injection of 2.5 mg/kg of DOX was used to generate a rat model of cardiotoxicity. All groups underwent ultrasonic examinations including standard echocardiography, 2D speckle tracking echocardiography (2D-STE), and MCE. Then all rats were sacrificed immediately for histopathological evaluation. Results A total of eight control rats and 32 DOX-treated rats were included in the study and grouped according to their treatment period. Decreased quantitative parameters of myocardial blood flow (MBF) (control vs. group 1: 133.31 ± 20.23 dB/s vs. 103.35 ± 21.60 dB/s, P = 0.048) and β (control vs. group 2: 11.17 ± 1.48/s vs. 7.15 ± 1.23/s, P < 0.001) were observed after 2 and 4 weeks of treatment, respectively, while left ventricular global strain (control vs. group 3: −23.67 ± 3.92% vs. −16.01 ± 3.40%, P = 0.002) decreased after 6 weeks of treatment and left ventricular ejection fraction (LVEF) (control vs. group 4: 82.41 ± 3.20% vs. 70.89 ± 9.30%, P = 0.008) decreased after 8 weeks of treatment. The main histopathological features are increased myocardial vacuolization and interstitial fibrosis and decreased myocardial microvessel density. Conclusion Compared with standard echocardiography and 2D-STE, MCE can accurately and non-invasively detect changes in early myocardial perfusion, demonstrating the clinical potential of continuous and dynamic monitoring of DOX-induced cardiotoxicity.